Difference scheme for differential-difference problems with small shifts arising in computational model of neuronal variability - Kodipaka, Mamatha; Emineni, Siva Prasad; Kolloju, Phaneendra (Zielona Góra: Uniwersytet Zielonogórski)
The solution of differential-difference equations with small shifts having layer behaviour is the subject of this study. A difference scheme is proposed to solve this equation using a non-uniform grid. With the non-uniform grid, finite-difference estimates are derived for the first and second-order derivatives. Using these approximations, the given equation is discretized.
Keywords: non-uniform grid; differential-difference equation; boundary layer